2014
DOI: 10.15835/nsb619191
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Vegetation Structure, Species Dominance and Plant Communities in South of the Eastern Desert-Egypt

Abstract: For two successive years, the floristic diversity and vegetation composition in the southern part of the Eastern Desert ofEgypt were investigated through four transects (3 crossing the Eastern Desert and one along the Red Sea). The data collected from 142 stands covering the study area included the species composition, functional groups, chorology and occurrences (Qvalues). A total of 94 plant species belonging to 33 different families were recorded, with Asteracea, Zygophyllaceae, Fabaceae,Poaceae, Chenopodia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 43 publications
10
8
0
Order By: Relevance
“…Moreover, the application of Canoncal Correspondence Analysis (CCA-biplot) between the position of vegetation groups on the ordination planes and soil variables of their stands indicated that, the most important soil factors affecting the distribution of vegetation in the studied areas were: the electrical conductivity, sulphate, pH, calcium carbonate, potassium adsorption ratio (PAR), cations, carbonate and bicarbonates. These results agreed more or less with those investigated by Galal and Fawzy [42], Salama et al [31], El-Amier and Abdulkader [32].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, the application of Canoncal Correspondence Analysis (CCA-biplot) between the position of vegetation groups on the ordination planes and soil variables of their stands indicated that, the most important soil factors affecting the distribution of vegetation in the studied areas were: the electrical conductivity, sulphate, pH, calcium carbonate, potassium adsorption ratio (PAR), cations, carbonate and bicarbonates. These results agreed more or less with those investigated by Galal and Fawzy [42], Salama et al [31], El-Amier and Abdulkader [32].…”
Section: Discussionsupporting
confidence: 93%
“…Groups A and B may represent the vegetation types of the Western Mediterranean coast of Egypt, while groups C and D may represent the WadiHagul. The identified vegetation groups in the present study were obviously similar to those investigated by Mashaly [28], Abd El-Ghani et al [39], Zahran et al [26], Salama et al [31] and El-Amier et al [33] [34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As indicated by CCA organic matter, Na, CaCO 3 , Mg, pH and salinity (electrical conductivity) contribute significantly to the distribution of plant species and plant communities in the study area. This finding had been reported by (Abd El-Ghani and Amer, 2003;Hegazy et al, 2004;SUMAMAD, 2014;Salama et al, 2014). Abd El-Ghani (1998) indicated that organic matter played an important role as a key element in soil fertility, and distribution of plant species.…”
Section: Discussionsupporting
confidence: 74%
“…The soil characteristics, particularly Na, Ca, K, Mg, Cl, SO 4 , pH, EC, gravels, and moisture contents, play essential roles in the vegetation groups in the Eastern Desert of Egypt [50]. The presence of some medicinal species in large groups of the Eastern Desert of Egypt reflects its capability to remain under various environmental systems [25,49].…”
Section: Discussionmentioning
confidence: 99%